2018
DOI: 10.1080/10942912.2018.1485032
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-based anthocyanin systems: effect of surfactants, cosurfactants, and its stability

Abstract: Anthocyanins exhibit natural antioxidants but exhibit poor stability and low oil solubility. Therefore, increasing the stability and fat solubility of anthocyanins is necessary to broaden their applications. In our experiment, an anthocyanin microemulsion system was constructed and its stability was investigated. At an oil phase and emulsifier ratio of 7:3, the hydrophilic oil-wet value reached 7.5 and the Km was 2:1. Furthermore, the microemulsion area was the largest. The bicontinuous region of the microemul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In general, surfactants alone cannot decrease the interfacial free energy sufficiently, so the addition of cosurfactant is necessary to produce thermodynamically stable NE systems [ 40 ]. The same finding has been reported for microemulsion-based anthocyanin systems that showed that the stability of the system was improved by increasing the concentration of cosurfactant [ 41 ].…”
Section: Resultssupporting
confidence: 81%
“…In general, surfactants alone cannot decrease the interfacial free energy sufficiently, so the addition of cosurfactant is necessary to produce thermodynamically stable NE systems [ 40 ]. The same finding has been reported for microemulsion-based anthocyanin systems that showed that the stability of the system was improved by increasing the concentration of cosurfactant [ 41 ].…”
Section: Resultssupporting
confidence: 81%
“…In a similar study, blueberry anthocyanins (BAE) were incorporated into a microemulsion system (BAE-ME) for encapsulation by Chen et al [60]. Through development of a pseudo ternary phase diagram composed of isopropyl myristate, Tween 80/Span 80 and ethanol as oil, surfactant, and cosurfactant, respectively, a stable W/O BAE-ME system with a particle size at 70 nm and anthocyanin content at 425.5 μg/g was prepared using an optimum oil phase-to-emulsifier ratio at 7:3, a surfactant-to-cosurfactant ratio at 2:1, and a hydrophilic-lipophilic balance (HLB) value at 7.5 (Figure 3G-1).…”
Section: Nanoemulsion-based Stability and Bioavailability Of Anthomentioning
confidence: 99%
“…Panels ( E ) and ( F1–3 ), stability of red cabbage anthocyanin-based solid-lipid nanoparticles (RCE-SLN) as affected by different pH (E) and temperatures at 25 °C (F1), 45 °C (F2), and 60 °C (F3) during storage for six days. Panel G1-4, TEM image (G1) of anthocyanin microemulsion prepared from blueberry extract (BAE-ME) along with its stability as affected by storage over a three month period at 4 °C (G2) and 25 °C (G3) as well as different ionic strengths (G4) (adapted with permission from references [54,58,59,60]).…”
Section: Figurementioning
confidence: 99%
“…According with particle concepts previously exposed at the introductive theories section, the transition from O/W type to W/O type takes place with changes in curvature orientation, experiencing the particular state of bicontinuity, with the occurring of structural modifications as can be seen in Figure 7. In the preformulation process, it is important to bear in mind the characteristics of the active substances, of the oil phase and S/CoS mixture and analyze their structure, to assess solubility data, according attention through the existence of possible interactions between molecules, along with pH or salinity influence, which may have further repercussions on the stability in time for the final product [258].…”
Section: Methods For Microemulsion Preparationmentioning
confidence: 99%
“…As a function of ME composition, particularly the surfactant molecules, the high values negative or positive of zeta potential will be correlated with a high stability, while low values determine a destabilized system with a reduced half-life [260]. In the preformulation process, it is important to bear in mind the characteristics of the active substances, of the oil phase and S/CoS mixture and analyze their structure, to assess solubility data, according attention through the existence of possible interactions between molecules, along with pH or salinity influence, which may have further repercussions on the stability in time for the final product [258].…”
Section: Methods For Microemulsion Preparationmentioning
confidence: 99%